Green skills integration practices of student teachers and cooperating teachers among secondary schools: Basis for enhanced instructional plan - Pecson, Ryan R.; Zabala, Arlene A. (Education and Development Research, 2025)
Student teachers and cooperating teachers are mandated to teach and impart to students the needed skills for them to become environmentally conscious citizens upholding sustainable and ecomonical practices. With that, the present study compares the green skills integration practices of student teachers and their cooperating teachers among secondary schools in a province in the Philippines as a basis for an enhanced instructional plan. The study utilizes the comparative design of quantitative research, wherein a questionnaire is used to gather data from 100 respondents (50 student teachers and 50 cooperating teachers) who voluntarily participated in the study. The study is implemented among public secondary schools in a province in the Philippines where the student teachers are deployed. As partners in the internship program, the cooperating teachers of the student teachers are included to compare their integration practices. A questionnaire is used to measure the green skills integration in the teaching practices. Descriptive statistics (mean and standard deviation) and inferential statistics (independent samples t-test) are used to analyze and identify significant differences in their integration practices. Findings reveal that cooperating teachers are more engaged in integrating green skills than student teachers, highlighting the need for enhanced training and support. A comprehensive learning plan, including targeted training and curriculum integration, is recommended to promote sustainable practices in education.